아버지의 자녀양육참여와 사회적 지원이 후속출산계획에 미치는 영향：어머니의 양육스트레스 매개를 중심으로 - 김종훈; 양소영; 성지현; Kim, Jonghoon; Yang, Soyoung; Sung, Jihyun (Korean Journal of child studies, 2013)
This study examined the effects of paternal participation in child care and social support on planning for a second childbirth, focusing on the mediating effect of the mother's parenting stress. The 887 subjects studied in this paper were mothers who have a first child, and were selected from a sample of the 2nd Panel Study of Korean Children(PSKC) by the Korea Institute of Child Care and Education(KICCE), conducted in 2009. Data was analyzed using a Structural Equation Model(SEM) to identify a structure and relationships among factors. The significance of indirect effects to test the mediating effect of maternal parenting stress was identified via bootstrapping. Results indicated that maternal parenting stress partially mediated the relationship between the father's participation in child care and planning for a second childbirth, and absolutely mediated the relationship between social support and planning for a second childbirth. The findings reveal the importance of reducing parenting stress, given its substantial impact on planning for a second childbirth.